1998
DOI: 10.1016/s0002-9270(98)00289-5
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and gastric neoplasia: correlations with histological gastritis and tumor histology

Abstract: Our results confirm a strong association between H. pylori and gastric carcinoma and adenoma. The intestinal-type gastric carcinoma is associated with atrophic gastritis and IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
1
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 0 publications
1
55
1
6
Order By: Relevance
“…37 Such mucosal atrophy in non-FAP patients with GA is generally considered to be induced by H pylori infection. 39 In our study however, H pylori was only detected in 58% of FAP patients with GA (table 2). Our H pylori negative patients with GA showed a significantly higher PG I/PG II ratio than in H pylori positive patients with GA (4.0 (0.8) v 2.7 (1.2); p<0.05).…”
Section: Discussioncontrasting
confidence: 57%
“…37 Such mucosal atrophy in non-FAP patients with GA is generally considered to be induced by H pylori infection. 39 In our study however, H pylori was only detected in 58% of FAP patients with GA (table 2). Our H pylori negative patients with GA showed a significantly higher PG I/PG II ratio than in H pylori positive patients with GA (4.0 (0.8) v 2.7 (1.2); p<0.05).…”
Section: Discussioncontrasting
confidence: 57%
“…Atrophic gastritis was associated with increased risk of both the intestinal and diffuse histological subtypes of non-cardia cancer but the association was stronger for the former as previously reported 37 39 40. Whereas the intestinal subtype is nearly always a consequence of atrophic gastritis and intestinal metaplasia, the diffuse histological subtype sometimes develops in a non-atrophic stomach with a strong genetic predisposition being an important factor in some of these cases 41 42…”
Section: Discussionmentioning
confidence: 67%
“…The present results suggest that infection with virulent H. pylori is associated with corpus dominant gastritis even in patients who do not develop gastric cancer. In a recent Japanese study, higher gastritis scores were observed for fundic mucosa than for pyloric mucosa both in patients with intestinal-type cancer and in control subjects [8]. Severe expression of corpus gastritis does not therefore seem to be a specific characteristic of patients with gastric cancer in Japan.…”
Section: Discussionmentioning
confidence: 87%